45 UMP BJTU JPA sponsored students depart for China - Mimi Rabita, Abdul Wahit (2023)
SEPANG, 13 February 2023 - A total of 45 students of the Dual Degree Programme of Universiti Malaysia Pahang (UMP) and Beijing Jiaotong University (BJTU) China departed to China recently to continue their studies for two years there.